EVA-PVA binder system for polymer derived mullite made by material extrusion based additive manufacturing. Issue 2 (February 2023) - Sarraf, Fateme; Hadian, Amir; Churakov, Sergey V.; Clemens, Frank
Abstract: Low processing temperature of preceramic polymers (PCPs) makes them attractive for material extrusion based additive manufacturing (MEX-AM), earlier called fused deposition modeling (FDM). Fabrication of bulk polymer derived ceramics is challenging due to gas evolution during crosslinking leading to pores and cracks in final product. Mixture of ethylene vinyl acetate (EVA) and polyvinyl alcohol (PVA) was successfully used to generate open porosity before crosslinking step. For 3D printing, a pellet extruder was used and a PVA binder content of 50 vol% was essential for succcessful solvent debinding process in water. The effect of PVA content and different EVA grades on printability and debinding behavior was studied. EVA with a lower melt flow index (MFI) showed better compatibility with PVA additive in terms of mixing and printing. EVA with higher vinyl acetate content seems to be more favorable for later thermal debinding processes because of its higher gas permeability.